Influence of Al doping on structural, dielectric, and ferroelectric properties of multiferroic BiFeO3 ceramics. Issue 6 (15th April 2019) - Bai, Peijia; Zeng, Yiming; Han, Jiao; Wei, Yongxing; Li, Mingwei
Abstract: Lead-free BiFe1- x Al x O3 ceramics with x = 0, 0.005, 0.01, 0.015, and 0.02 were synthesised via the traditional solid-state reaction method. The effects of Al doping on the crystalline structure, dielectric, and ferroelectric properties were investigated. X-ray diffraction results indicated that Al doping increased the secondary phases (Bi2 Fe4 O9 and Bi25 FeO39 ) when the Al content was above 0.015. Scanning electron microscopy images showed that the grain size in the BiFe1- x Al x O3 ceramics decreased from 1.6 to 0.45 µm with the increase of the Al content. Samples with a small amount of Al doping exhibited improvements in the remnant polarisation and dielectric constant compared with pure BiFeO3 . However, when the Al content increased, the dielectric constant decreased and the polarisation hysteresis loops become unsaturated. With the increase of the Al content, the TC increased and exceeded 500 °C, and the leakage current densities of the BiFe1- x Al x O3 ceramics first increased and then decreased. These changes of the electric properties were related to the decrease of the grains size, the generation of secondary phases, and the increase of carriers.